COPD Assessment Test (CAT) score as a predictor of major depression among subjects with chronic obstructive pulmonary disease and mild hypoxemia: a case–control study - Silva Júnior, José Laerte R (BMC Pulm Med, 2014)
BACKGROUND: Depression is a common comorbidity among patients with Chronic Obstructive Pulmonary Disease (COPD) and has a significant impact on the course of the disease. The aim of this study is to determine association between COPD Assessment Test (CAT) and major depression among clinically stable out-patient COPD subjects with mild hypoxemia. METHODS: Case–control study. Cases were 30 patients with major depression and controls were 30 patients without depression. Major depression was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders criteria by a psychiatric evaluation. All possible predictive variables were included in a multivariate logistic regression model to assess the association between major depression and each independent variable, while controlling for the sleep parameters. RESULTS: CAT score >20 was associated with major depression (OR 7.88; 95% CI 1.96 - 31.7; p = 0.004). CONCLUSION: CAT score >20 was associated with major depression, suggesting CAT as a predictor variable of major depression among COPD patients with mild hypoxemia, and indicating that an additional specific evaluation for the presence of major depression should be done.